The Role of Green Marketing Effect, Price On Millenial Consumers Green Purchase Behaviour Mediated by Green Brand Equity - Firmansyah, Fani; Endah Purnamasari, Puji; Farida, Lailatul; Prajawati, Maretha Ika (Indonesian Journal of Business and Entrepreneurship, 2026)
Backgrounds: Price on the purchasing behavior of environmentally friendly products by millennial consumers in Malang, with green brand equity as a mediating variable. Green marketing involves product development and marketing strategies. Purpose: This study aims to examine how green marketing and price affect the purchasing decisions of the millennial generation, with green brand equity as a mediating variable. Green marketing is currently a reliable driver of the development and desire for proper brand equity. Design/methodology/approach: This study used a quantitative approach. Students in Malang who had utilized PT. Unilever home care products comprised the study population. Quota sampling was used in this investigation. In this study, questionnaires and literature reviews were used as data collection methods. PLS structural model analysis was also performed in this study using SmartPLS 4.0 software. Findings/Result: This study found that positive price assessments and green marketing significantly impact millennial customers’ decisions to purchase environmentally friendly products. Additionally, it has been shown that green brand equity plays a substantial mediating role in the interaction between price, green marketing, and customer purchasing decisions. Businesses must focus on green marketing strategies and build green brand equity to attract millennial consumers and increase the sales of eco-friendly products. Businesses that successfully apply this tactic can improve their competitiveness and support environmental sustainability. Conclusion: This study shows that green marketing and positive price perception significantly influence millennials’ green product purchasing decisions. In addition, green brand equity is an important mediator in the relationship between green marketing, price, and consumer purchasing decisions. Companies must focus on green marketing strategies and build green brand equity to attract millennial consumers and increase green product sales. Companies that successfully implement these strategies can gain competitive advantages and contribute to environmental sustainability. Originality/value: This study examines the influence of green marketing and price on green purchase behavior among millennial consumers in Malang, with green brand equity as a mediating variable. These variables have been widely studied in sustainable marketing studies, but the combination of green marketing, price, and green brand equity simultaneously and in the context of local millennial demographics provides an opportunity for originality. Keywords: green marketing, price affect, green brand equity, green purchase behaviour, environmental sustainability